Parâmetros ecocardiográficos e peptídeo natriurético cerebral em pacientes no pósoperatório tardio de tetralogia de Fallot - Tatani, Solange Bernardes [UNIFESP] (2009)
Background: Although the residual lesions after surgical correction of tetralogy of Fallot (TOF) can be evaluated by Doppler echocardiography (DE), the relation of DE parameters with the proBNP level, a potential biomarker of right ventricle overload, is not well known. The objective this study was to evaluate the DE parameters and their relation to proBNP levels. Methods: proBNP plasma level and Doppler echocardiography parameters were obtained in the same day in 49 patients later after repair of TOF (mean age of 14.7 years, 51% female, mean PO time of 9.5 years). The DE parameters studied were the dimensions of the right atrium (RA) and ventricle (RV), RV diastolic and systolic function and residual pulmonary lesions. The relation between them and proBNP levels were analyzed and the cutoff values of DE parameters for elevated proBNP determined. Results: proBNP was elevated in 53% and correlated with RV diastolic diameter (r=0.41; p=0.003), RA longitudinal (r=0.52; p=0.0001) and transversal (r=0.47; p=0.001) diameters, pressure half time of pulmonary regurgitation (PR) velocity (PHT) (r= -0.42; p=0.005) and the PR index (r=-0.60; p<0.001). By multivariate analysis the PR index (r=-597; p=0,001; CI: -913.2 to –280.8) and RA longitudinal (r=7.74; p<0,001; CI 4.18 to 11.31) were independent predictors of elevated proBNP. PHT lower than 64 ms (0.76) and PRi lower than 0.65 (0.81) had the best accuracy for elevated proBNP. Conclusion: proBNP may be increased in patients after surgical repair of TOF, correlated with the size of right cardiac chambers and the severity of PR.